Philippine Basic Education System : Strengthening Effective Learning During the COVID-19 Pandemic and Beyond - Cho, Yoonyoung; Kataoka, Sachiko; Piza, Sharon (World Bank, Washington, DC, 2021)
School closures and learning loss during the Coronavirus (COVID-19) pandemic can have a long-term negative impact on the current cohort of school children. Global evidence from past health and disaster-related emergencies show that the impact extends well beyond the period of the disaster or pandemic. It is also likely to affect the children’s economic potential and productivity in adulthood, thus undermining the country’s competitiveness. This policy note analyzes key issues related to the current schooling and learning situation and proposes policy options to prepare for in-person schooling when this is possible. Two nationwide surveys in the Philippines provide a snapshot of the conditions of education in the country: the High Frequency Monitoring (HFM) Household Survey carried out in December 2020 and the Coronavirus (COVID-19) Low Income Household Panel and Economic (HOPE) Survey targeting poor and near-poor households carried out in October 2020. The key issues emerging from these data and policy recommendations are summarized in this report.